2011
DOI: 10.1007/s11357-011-9335-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased active von Willebrand factor during disease development in the aging diabetic patient population

Abstract: Type 2 diabetes is known to cause endothelial activation resulting in the secretion of von Willebrand factor (VWF). We have shown that levels of VWF in a glycoprotein Ib-binding conformation are increased in specific clinical settings. The aim of the current study is to investigate whether active VWF levels increase during aging and the development of diabetes within the population of patients suffering from type 2 diabetes. Patients and controls were divided into two groups based on age: older and younger tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…These substantially include cancer, 118 sedentary lifestyle, 119 autoimmune disorders, 120 and diabetes. 54,121 Nevertheless, the association of elevated procoagulant status with increased thrombosis risk is also evident, given the recognized association of many of the hemostasis markers described here with thrombosis and the simple fact that thrombosis rates increase with aging. As briefly mentioned in the introduction, the findings reported here have also additional important implications for clinical and laboratory practice.…”
Section: General Discussion: Implications For Clinical and Laboratorymentioning
confidence: 83%
See 1 more Smart Citation
“…These substantially include cancer, 118 sedentary lifestyle, 119 autoimmune disorders, 120 and diabetes. 54,121 Nevertheless, the association of elevated procoagulant status with increased thrombosis risk is also evident, given the recognized association of many of the hemostasis markers described here with thrombosis and the simple fact that thrombosis rates increase with aging. As briefly mentioned in the introduction, the findings reported here have also additional important implications for clinical and laboratory practice.…”
Section: General Discussion: Implications For Clinical and Laboratorymentioning
confidence: 83%
“…53 Increasing levels of VWF with aging may also be confounded by additional age associated pathologies including, for example, diabetes. 54 Changes in VWF with age have a particular implication in altered perceptions of VWD diagnosis, as briefly explored at the end of this article.…”
Section: Von Willebrand Factormentioning
confidence: 99%
“…VWFpp and VWF levels have also been used to identify endothelial cell activation in diabetes. 67,69,[75][76][77] A significant increase in VWF and VWFpp were identified in insulin-dependent diabetic patients with microalbunimuria or overt diabetic nephropathy. 67,75 The study by Verrotti et al demonstrated that endothelial dysfunction is present at least 2 years before the development of persistent microalbuminuria.…”
Section: Assay Of Plasma Vwfpp: Clinical Utility Vascular Disorders Amentioning
confidence: 95%
“…The increasing knowledge regarding how and how soon the endothelium can be injured and the release of a large variety of biologic markers has recently led to the assumption that these markers can be a surrogate for endothelial dysfunction. 21,22 Vascular endothelium damage is characterised by an increase of endothelium-derived regulatory proteins. Plasma markers of endothelial dysfunction like von Willebrand factor (vWF), cellular adhesion molecules (CAD), endothelin 1 (ET1), selectin, thrombomodulin may be useful to investigate early endothelium involvement.…”
Section: Discussionmentioning
confidence: 99%